Finite element stress analysis on natural gas motorcycle intake manifold - Yaacob, Zulkefli; Mohsin, Rahmat; Abd Majid, Zulkifli; Teh, Irene Hui Lynn; Baharim, Rosdi (Penerbit UTM Press, 2008)
Stress analysis is an essential part of the design process and is also an indispensable tool for optimizing structural design to meet multidisciplinary performance requirements. The purpose of this study is to determine natural vibration frequency of intake manifold on the natural gas motorcycle by using finite element modal analysis. Besides that, the stress and displacements of the manifold structure are also been determined. When the motorcycle engine is running, the engine will cause some vibration due to unbalance condition of the engine. Vibration created by the engine will be transmitted to all neighboring component including intake manifold as well as the air fuel mixer. Intake manifold is next to the engine which is the source of the vibration. Thus, it takes greater impact of the transmitted vibration as compare to other components. Computer simulation technique using Finite Element method has been used to simulate this problem. Finite Element structure analysis was employed to study the stress distribution and natural frequency of the intake manifold. Finite Element model of the intake manifold is developed and analyzed. The effect of localize stiffening with ribs on intake manifold is considered to reduce the level of the vibration. It was found that by adding a stiffened rib to the manifold structure, the natural frequencies are increased. This may due to the stiffening of the manifold structure which dominates its vibration characteristics. Moreover, the strength of the manifold structure is also increased by adding a rib.